PENERAPAN MODEL PEMBELAJARAN KOOPERATIF PENDEKATAN STRUCTURAL NUMBERED HEADS TOGETHER (NHT) UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIKA SISWA KELAS VII1 SMP NEGERI 17 PEKANBARU - Popy Yusrianti; Jalinus Jalinus; Suhermi Suhermi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: The background of this research is the result of learning mathematics of class student VII1 SMP Negeri 17 Pekanbaru which is still under the minimum mastery criteria with a persentage of 30,5 % only 11 students from 36 students who achieve the minimum mastery criteria on the subject matter of the algebra. The purpose of this research aims to improve the learning process and increase the student’s mathematics learning outcomes through the implementation of Cooperative learning structured approach Numbered Heads Together. This type of research is the Classroom Action Research with two cycle, who conducted in class VII1 SMP Negeri 17 Pekanbaru in the second semester of the 2018/2019 academic year. Research subject as many 36 students, consist of 17 boys and 19 girls. The research instrument consists of learning devices and instrument data collectors. Learning device used is Syllabus, Lesson Plan and Worksheet. The instrument data collector used in this research is the observation sheet and math achievement test. The observation sheet was analyzed whit descriptive qualitative while the test of mathematics learning outcomes was analyzed statistically. Based on deskriptive qualitative analiysis showed that implementation of learning process on cycle II had happened improvement from implementation on cycle I. Weakness on cycle I is improved on implementation cycle II according with planning of improvement after reflection cycle I. Number of students that reach Minimum Mastery Criteria increase from basic score to daily test II. The number of students who reach Minimum Mastery Criteria on basic scor, daily test I and daily test IIare respectively 16 person (44,4 %), 21 person (58,3 %) and 27 person (75 %). Results of this research indicates that application of the Cooperative learning structured approach Numbered Heads Together can improve learning process and increase mathematics learning outcomes from the students at class VII6 SMP Negeri 17 Pekanbaru in the second semester academic years 2018/2019.Key Words: Students’ Math Achievement, Cooperative Learning Structural Approach of Numbered Heads Together, Classroom Action Research.